Design and construction of a secure ID-card system using robust image hashing - Öztemel, Mehmet. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
We present a very simple, cryptographically secure, inexpensive and contactless biometric identity veri cation system. The system we propose is a printout of individual's biometric feature (pictorial data) such as face, hand, iris and a textual message. Furthermore, an HF RFID tag that involves RSA signature, compressed representations of the textual and pictorial data printed on a PVC card provides contactless communication. Digital signature is created using the private key of the signer. Veri cation is performed by an intelligent device involving a USB Camera and a RFID Reader. There are mainly two processes: certi cation and authentication. ID is certi ed in the following way. First, the textual data is hashed using a cryptographically secure hashing algorithm such as MD5. Next, the pictorial data is hashed using robust hashing algorithms. Finally, hashed pictorial data, text and RSA signature of formers' are encoded into the RFID tag in ID card. Veri cation is performed by a simple and o - line device that contains the public key of the issuer. The signature, hashed textual and pictorial data are received from RFID tag via RFID reader, authenticity of the signature is checked. On the other side, a snapshot of the ID card is taken via USB camera. The image taken is then recti ed to obtain textual and facial data. The textual data on the card is converted into a text-string using reliable optical character recognition. Robust image hashing methods are applied to the facial data. A comparison score is obtained comparing the resulting hash values with the hash values obtained from RFID tag. The identity document is authentic if the score is above the threshold.
Keywords: Radio frequency identification systems.; Identification cards.; Hashing (Computer science)